An Experimental Study on Transient Characteristics of a Nuclear Reactor Coolant Pump in Coast-Down Process Under Power Failure Condition - li, Wang X.; Wei, Xu; sheng, Zhu R.; yuan, Zhao Y.; zhou, Zhong H. (Frontiers in Energy Research, 2020)
In order to study the transient characteristics of a nuclear reactor coolant pump in coast-down process under power failure condition, a transient test device for the nuclear reactor coolant pump is set up. This study investigates the effects of the rotor of the nuclear reactor coolant pump and the circuit characteristics on the nuclear reactor coolant pump during the coast-down process by changing the rotary inertia of the flywheel and the resistance of the pipe system. The results show that the greater the moment of inertia is, the more slowly rotational speed, flow, and lift get down in the same coast-down period. The change in the pipe resistance has little effect on the rate of decline in the coast-down process, but it has a great influence on the descent speed of the flow rate and lift. When the pipe resistance is small, the corresponding flow rate decreases faster, but it is slower for the corresponding lift. The results are of great significance in controlling the stability and reliability of the nuclear reactor coolant pump in the coast-down process.